Frazeologija v šoli - drugič - Kržišnik, Erika (Jezik in slovstvo, 2015)
The article presents and interprets the results of a survey carried out for a second time in 2014, some 27 years after its initial execution. The sample included 234 first-year secondary school students (four classes) and fourth-year secondary school students (five classes). Three of the secondary schools were grammar schools (two in Ljubljana and one in Celje) and one was a technical school in Ljubljana. Originating in the 1980s, the survey contains Slovenian phrasemes that secondary school students now consider slightly more traditional; we therefore added some phrasemes frequently used and current today. We monitored the knowledge of phrasemes in terms of form, meaning and use. The results
Keywords: Slovene; slovenščina; frazeologija; phraseology; ankete; srednje šole; časovna zaznamovanost